Pharmacokinetic Parameters and Estimating Extra-Label Tissue Withdrawal Intervals Using Three Approaches and Various Matrices for Domestic Laying Chickens Following Meloxicam Administration - Richards, Emily D.; Dutch, Rachel S.; Burmas, Nathaniel C.; Davis, Jennifer L.; Lin, Zhoumeng; Clapham, Maaike O.; Wetzlich, Scott E.; Tell, Lisa A. (Frontiers in Veterinary Science, 2022)
Meloxicam is commonly prescribed for treating chickens in backyard or small commercial operations despite a paucity of scientific data establishing tissue withdrawal interval recommendations following extra-label drug use (ELDU). Historically, ELDU withdrawal intervals (WDIs) following meloxicam administration to chickens have been based on the time when meloxicam concentrations fall below detectable concentrations in plasma and egg samples. To date, no studies have addressed tissue residues. ELDU WDIs are commonly calculated using terminal elimination half-lives derived from pharmacokinetic studies. This study estimated pharmacokinetic parameters for laying hens following meloxicam administration and compared ELDU WDIs calculated using tissue terminal elimination half-lives versus those calculated using FDA tolerance and EMA’s maximum regulatory limit statistical methods, respectively. In addition, ELDU WDIs were calculated using plasma meloxicam concentrations from live birds to determine if plasma data could be used as a proxy for estimating tissue WDIs. Healthy domestic hens were administered meloxicam at 1 mg/kg intravenous (IV) once, 1 mg/kg orally (PO) once daily for eight doses or 1 mg/kg PO twice daily for 20 doses. Analytical method validation was performed and meloxicam concentrations were quantified using high-performance liquid chromatography. In general, the terminal elimination technique resulted in the longest ELDU WDIs, followed by the FDA tolerance and then EMA’s maximum residue limit methods. The longest ELDU WDIs were 72, 96, and 384 (or 120 excluding fat) h for the IV, PO once daily for eight doses, and PO twice daily for 20 doses, respectively. Plasma data are a possible dataset for estimating a baseline for tissue ELDU WDI estimations when tissue data are not available for chickens treated with meloxicam. Finally, pharmacokinetic parameters were similar in laying hens to those published for other avian species.